ANALISIS SEMIOTIKA IKLAN JUDITH WILLIAMSON PADA FEED IG @JCOINDONESIA “COUNTING DAYS TO I LOVE JCO 2022” - Zaenudin Mukhtar (UNIVERSITAS NUSA PUTRA, 2022)
This study seeks to explore the use of advertising semiotics in @jcoindonesia's feed design with the theme